Ruddlesden–Popper 2D Chiral Perovskite‐Based Solar Cells. Issue 8 (12th August 2022) - Shpatz Dayan, Adva; Wierzbowska, Małgorzata; Etgar, Lioz
Abstract : 2D Perovskites In article number 2200051, Adva Shpatz Dayan, Małgorzata Wierzbowska and Lioz Etgar, demonstrate two dimensional (2D) chiral perovskites. The chirality is manifested at pure 2D perovskite with anisotropy factor (gabs) which decreased by an order of magnitude when decreasing the dimensionality achieving a value of 0.0062 for pure 2D. The chiral low dimensional perovskite affects the current density of the solar cell.